2016
DOI: 10.1155/2016/1260702
|View full text |Cite
|
Sign up to set email alerts
|

Land-Cover Legacy Effects on Arbuscular Mycorrhizal Abundance in Human and Wildlife Dominated Systems in Tropical Savanna

Abstract: Arbuscular mycorrhizal fungi (AMF) can be important mutualists to plant hosts in acquiring soil nutrients. Past work has not explored whether previous land-cover history influences current AMF abundance in croplands and whether different land-cover histories in grazed but not cultivated areas influence AMF. This study was conducted to assess the effects of land-cover history in and near Serengeti National Park on AMF abundance in areas with three different land uses. The results showed that land-cover history … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…Nutrient-rich top soils tend to be eroded and to leach nutrients during heavy rains when herbaceous cover is being removed [23]. However, this perception is in contrast to [24,25] that indicated that elephant dung can increase soil nutrients. Across the three study divisions, crop raiding was the most frequently recorded and mentioned HEC.…”
Section: Human Perception Human-elephant Conflict Incidents Andmentioning
confidence: 94%
“…Nutrient-rich top soils tend to be eroded and to leach nutrients during heavy rains when herbaceous cover is being removed [23]. However, this perception is in contrast to [24,25] that indicated that elephant dung can increase soil nutrients. Across the three study divisions, crop raiding was the most frequently recorded and mentioned HEC.…”
Section: Human Perception Human-elephant Conflict Incidents Andmentioning
confidence: 94%
“…The remarkable transformations of LULC in the ecosystem and buffer area were mainly associated with expansion of settlements resulting from human population growth. Human activities have transformed significant natural vegetation (including woodland) in the ecosystem into agricultural land and grasslands in the ecosystem [12,111,112]. Vegetation clearing for cultivation and settlement transforms woodland into grassland, shrubland and other cover types [113].…”
Section: Lulc Cover Trajectoriesmentioning
confidence: 99%
“…Vegetation clearing for cultivation and settlement transforms woodland into grassland, shrubland and other cover types [113]. The conversion of grassland to agriculture is a widespread phenomenon in the SNP [112] and elsewhere, including rangelands in the United States [114]. Specifically, browsing and rainfall interactions transformed shrubland to grassland in the Maasai Mara ecosystem (1979)(1980)(1981)(1982)(1983)(1984)(1985)(1986)(1987)(1988)(1989)(1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998) in Kenya [98,115].…”
Section: Lulc Cover Trajectoriesmentioning
confidence: 99%
“…Reducing the number of MA can cause irreversible damage to habitats that will later impact the wider ecosystem services (Chen, Liu, Bi, & Feng, 2014;Solaiman, Abbott, & Varma, 2014). The study of the diversity and function of MA species is very important considering the impact of changes in land use on an ecosystem can reduce land productivity (Moora et al, 2014;Neuenkamp, Zobel, Lind, Gerz, & Moora, 2019;Soka & Ritchie, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The P was not available for plants extracted from the soil by MA under a symbiosis scheme with the hosted plant (Chen, Liu, Bi, & Feng, 2014: Solaiman, Abbott, & Varma, 2014. The increasing number of MA spores provided rapid nutrients supplied by mycorrhiza to crop (Moora et al, 2014;Soka & Ritchie, 2016). According to Sukmawaty, Hafsan, & Asriani (2016), the presence of MA colonization in plant roots can increase drought tolerance.…”
Section: Introductionmentioning
confidence: 99%